2005
DOI: 10.1161/01.hyp.0000161881.02361.11
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Genome Scan for Loci Linked to Blood Pressure Levels and Trends Since Childhood

Abstract: Abstract-Genetic loci influencing the long-term levels and trends of blood pressure over time were investigated using 775 white siblings, ages 13 to 43 years, enrolled in the Bogalusa Heart Study, and 357 microsatellite markers on the 22 autosomal chromosomes. Subjects had been examined serially 2 to 12 times with 4365 serial observations over an average of 22 years from childhood to adulthood. Total and incremental area under the curve was calculated based on a cubic growth curve and used as long-term levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 40 publications
(48 reference statements)
0
35
0
Order By: Relevance
“…1 The genes encoding DRD1 and GRK4 localize to chromosomes 5q35.1 3 and 4p16.3, 4 respectively. The GRK4 gene locus is embedded in a cluster on chromosome 4p16, which is associated with hypertension 5,6 and also includes ␣-adducin (ADD1). To our knowledge, there are no studies showing significant genome-wide linkage of hypertension with the DRD1 locus, although a genome-scan meta-analysis 7 identified 5q as a suggestive region.…”
mentioning
confidence: 99%
“…1 The genes encoding DRD1 and GRK4 localize to chromosomes 5q35.1 3 and 4p16.3, 4 respectively. The GRK4 gene locus is embedded in a cluster on chromosome 4p16, which is associated with hypertension 5,6 and also includes ␣-adducin (ADD1). To our knowledge, there are no studies showing significant genome-wide linkage of hypertension with the DRD1 locus, although a genome-scan meta-analysis 7 identified 5q as a suggestive region.…”
mentioning
confidence: 99%
“…22 The Bogalusa Heart Study showed significant evidence of linkage to 2p13 at 73 cM for longterm (child to young adult) levels of diastolic bp. 23 Additionally, a 140 to 170 cM interval has been linked to preeclampsia in Finnish 24 and Australasian 25 populations, whereas linkage peaks at 40 to 140 cM and at 230 cM, obtained with 2 independent Family Blood Pressure Program (FBPP) Studies, 26,27 immediately flank that of the candidate interval (155 to 233 cM) suggested by analysis of the Kyrgyz pedigree in this study.…”
Section: Discussionmentioning
confidence: 53%
“…Rowing includes the components of endurance and resistance training, but there is an upper and lower body imbalance that could influence to systolic blood pressure (16,17). On the other hand, this study cannot reject the possibility genetic predisposition to higher blood pressure during exercise (18,19).…”
Section: Discussionmentioning
confidence: 80%